Evaluasi Website Repositori Institusi Universitas Surabaya - Ulum, Amirul (Pustakaloka, 2015)
TheÂ  developmentÂ  ofÂ  institutionalÂ  repositoriesÂ  (IRs)Â  in Indonesia within the broader framework of open access has significant impact on preserving intellectual capital and scholarly communication. InstitutionalÂ  repositoriesÂ  playÂ  aÂ  fundamentalÂ  roleÂ  inÂ  centralizing, preserving,Â  andÂ  makingÂ  accessibleÂ  institutionâsÂ  intellectualÂ  capital. Evaluation of the system is to determine the functionality the system to meet the users need. Using a descriptive analysis this study wants to evaluate institutional repositories of University of Surabaya. The result is usefull for institution to develop the repository systems.